Bioleaching of Chalcopyrite Waste Rock in the Presence of the Copper Solvent Extractant LIX984N - Liu, Xiaohui; Li, Yuhong; Cao, Jianfeng; Zeng, Zhenshun; Liu, Xiaorong; Zhang, Ruiyong; Li, Qian; Sand, Wolfgang (Frontiers in Microbiology, 2022)
Heap bioleaching, the solubilization of metal ions from metal sulfides by microbial oxidation, is often combined with solvent extraction (SX) and electrowinning to recover, e.g., copper from low-grade ores. After extraction, the leaching solution is recycled, but the entrained organic solvents may be toxic to the microorganisms. Here Acidithiobacillus ferrooxidans, Leptospirillum ferrooxidans, and Sulfobacillus thermosulfidooxidans were selected to perform bioleaching of chalcopyrite waste rock in the presence of the SX reagent (2.5% v/v LIX984N in kerosene). Possibly inhibitory effects have been evaluated by copper extraction, bacterial activity, number of actively Fe(II)-oxidizing cells, and biofilm formation. Microcalorimetry, most probable number determination, and atomic force microscopy combined with epifluorescence microscopy were applied. The results show that 100 and 300 mg/L SX reagent could hardly inhibit At. ferrooxidans from oxidizing Fe2+, but they seriously interfered with the biofilm formation and the oxidization of sulfur, thereby hindering bioleaching. L. ferrooxidans was sensitive to 50 mg/L SX reagent, which inhibited its bioleaching completely. Sb. thermosulfidooxidans showed different metabolic preferences, if the concentration of the SX reagent differed. With 10 mg/L LIX984N Sb. thermosulfidooxidans preferred to oxidize Fe2+ and extracted the same amount of copper as the assay without LIX984N. With 50 mg/L extractant the bioleaching stopped, since Sb. thermosulfidooxidans preferred to oxidize reduced inorganic sulfur compounds.